2021
DOI: 10.1096/fj.202002395rr
|View full text |Cite
|
Sign up to set email alerts
|

ACKR2 limits skin fibrosis and hair loss through IFN‐β

Abstract: Skin fibrosis is a deleterious outcome of a dysregulated and progressive healing phase of inflammation. 1,2 Resolution of inflammation is essential for proper wound healing and limits tissue repair short of exuberant fibrotic scarring. [3][4][5] During the resolution of inflammation, infiltrating inflammatory monocytes differentiate to reparative phagocytic macrophages. 6,7 However, if not controlled in a timely fashion, these macrophages can also promote tissue fibrosis. 8,9 Extracellular matrix (ECM) protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Additionally, recent knockout studies in ACKR2 −/− mice revealed the importance of interferon-beta in the rescue of collagen organization and hair loss. 22 However, due to alopecia reports in the literature and prescription label for the interferons, further exploration is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, recent knockout studies in ACKR2 −/− mice revealed the importance of interferon-beta in the rescue of collagen organization and hair loss. 22 However, due to alopecia reports in the literature and prescription label for the interferons, further exploration is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship with VEGFA-VEGFR signaling is consistent with previously reported observations on ACKR2 expression in lung endothelial cells ( Hansell et al, 2020 ). Furthermore, TGFβ signaling, which has known influences on ACKR2 expression ( McKimmie, et al 2013 ) plays a role in skin fibrosis ( Butenko, Ben Jashar et al, 2021 ). The reported role of ACKR2 in the systemic regulation of glucose tolerance, accompanied by reduced insulin secretion and increased whole body insulin sensitivity ( Zheng, et al 2016 , Fioravante et al 2019 ) is consistent with the identified enrichment in the insulin signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…After bleomycin exposure, Ifnb –/– mice showed increased pro-fibrotic indices. There is evidence to indicate that ACKR2 is one of the key players in preventing chronic inflammation-induced skin scarring caused by promoting IFN-β production ( 117 ).…”
Section: The Role Of Ackr2 In Diseasesmentioning
confidence: 99%